Seismic Vulnerability Index Analysis In The Sub-District Of Lake Kembar, Solok Regency, As An Effort To Determine The Potential Aslided Area Using HVSR Method - Percindira, Ella Dwi; Syafriani, Syafriani; Hamdi, Hamdi; Dwiridal, Letmi (Department of Physics, Universitas Negeri Padang, 2023)
Nagari Kampung Batu Dalam, Danau Kembar District, experienced a landslide caused by high rainfall and steep topography (slope). However, there needs to be more information regarding the classification of landslide potential levels that will occur. So it is essential to carry out this study to determine the soil type, sediment depth, and seismic vulnerability index. Ten microtremor data are scattered in this area. Measurements are carried out using an MAE Sysmatrack and 3D Seismic Surface Sensor, and this is done because these measurements are not difficult to carry out and do not require a large amount of money. However, there is an abundance of information that can be analyzed. Microtremor signal data were processed using Geopsy software with the Horizontal to Vertical Spatial Ratio (HVSR) method and soil profiles which stated the parameters of the shear wave velocity (Vs) and the depth of the sediment layer (H) using the ellipticity curve method. The results obtained show that the f0 value ranges from 0.6-4.37 Hz, the Amplification Factor ranges from 1.4-17.1, the sediment thickness (H) ranges from 24.5-240.8 m, and the seismic susceptibility index ranges from 1.72E-04 - 3.21E-02 cm/s2. Based on the mapping and modeling, it shows that alluvial rocks dominate the locations that have the potential for landslides.